Species composition of heterocytous cyanobacteria in some types of cultivated soils in Nghe An province - Dien, Nguyen Duc; Vinh, Nguyen Le Ai; Hanh, Vo; Thanh, Nguyen Trung (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 1DO - 10.25073/2588-1140/vnunst.4706, 2018)
On the basis of morphological analyses of cyanobacteria in 60 cultivated soil samples collected from 30 sites in 10 districts of Nghe An province, 22 species of heterocytous cyanobacteria were identified according to the taxonomic system of Komárek (2013). These species belonged to 5 families and 9 genera. The genera with highest number of species were Nostoc (8 species) and Scytonema (5 species); 19 species distributed in paddy rice soils and 6 species were in terrestrial soils for cultivating industrial plants. Two species, their distributions were the first time recognized in Vietnam, were Westiellopsis prolifica and Nostoc gelatinosum . Keywords Heterocytous cyanobacteria, cultivated soil, Nghe An, Westiellopsis prolifica , Nostoc gelatinosum References [1] Desikachary T.V., Cyanophyta, Indian Council of Agriculture Research, New Delhi, 1959. [2] Komárek J., Band 19/3 – Cyanoprokaryota. Heterocytous Genera in Freshwater flora of Central Europe, Edited by B. Büdel, G. Gärtner, L. Kriennitz, M. Schagerl, Heidelberg: Spektrum Akademischer Verlag, 2013. [3] Dương Đức Tiến, Phân loại vi khuẩn lam ở Việt Nam, Nhà xuất bản Nông nghiệp, Hà Nội, 1996. [4] Phung T.N.H., Coute A. and Bourrelly P., Les Cyanophycées du delta du MéKong (Viet-Nam), Nova Hedwigia, 54 (1992) 403–446. [5] Võ Hành, Đỗ Thị Trường, Kết quả nghiên cứu bước đầu về khả năng cố định nitơ phân tử của một số loài vi khuẩn trong đất trồng lúa ở huyện Hòa Vang, thành phố Đà Nẵng, Tạp chí Sinh học 23 3c (2001) 10–13. [6] Nguyễn Lê Ái Vĩnh, Võ Hành, Vi khuẩn Lam (Cyanobacteria) trong đất trồng lúa của huyện Thạch Hà, tỉnh Hà Tĩnh, Tạp chí Sinh học, tập 23 3 (2001) 29–42. [7] Hồ Sỹ Hạnh, Thành phần loài vi khuẩn lam (Cyanobacteria) trong một số loại hình đất trồng tỉnh Đắk Lắk và tỉnh Đắk Nông, Tạp chí Sinh học 32 3 (2010) 44–51. [8] Nguyễn Đức Diện, Nguyễn Lê Ái Vĩnh và Võ Hành, Danh lục các loài vi khuẩn lam có tế bào dị hình (heterocytous cyanobacteria) trong đất trồng ở Việt Nam theo hệ thống phân loại của J. Komárek (2013), Báo cáo khoa học về sinh thái và tài nguyên sinh vật, Hội nghị khoa học toàn quốc lần thứ 7, Hà Nội, Nhà xuất bản khoa học tự nhiên và công nghệ (2017) 84 – 90. [9] Dương Đức Tiến, Ngành Vi khuẩn lam trong Danh lục các loài thực vật Việt Nam, Tập 1, Trung tâm nghiên cứu tài nguyên và môi trường - Đại học Quốc Gia Hà Nội, Nhà xuất bản Nông nghiệp Hà Nội, 2001. [10] Hồ Sỹ Hạnh, Võ Hành, Đặng Diễm Hồng và Dương Đức Tiến, Phát hiện mới về chi Westiellopsis Janet ở Đắc Lắk cho hệ vi tảo Việt Nam, Tạp chí Công nghệ Sinh học 3 (2005) 509-516.